2016
DOI: 10.14710/ik.ijms.21.2.65-76
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Sediment Profile in Shrimp Culture with Different Sediment Redox Potential and Stocking Densities Under Laboratory Condition

Abstract: Sediment quality has been considered as one of the prime factors influencing the environment quality that support maximum shrimp production.The aim of the study was toevaluate the effects of sediment redox potential and shrimp stocking density on the profile of some sediment and water quality parameters. Two factors randomized factorial design was applied, with stocking density (60 and 120 shrimps.m-2) as the first variable and sediment redox potential (-65 mV, -108 mV and -206 mV) as the second variable. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…The increase in accumulated organic matter leads to a reduction in redox potential (moving towards reduced condition), which is an index of the degree of oxidation and reduction condition of pond sediment (Wilding, ). The redox potential of lower than −206 mV significantly reduces the DO concentration in the SWI and increases the H 2 S in the water column (Wiyoto, Sukenda, Harris, Nirmala, & Djokosetiyanto, ), which affects the total concentration of some major elements.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in accumulated organic matter leads to a reduction in redox potential (moving towards reduced condition), which is an index of the degree of oxidation and reduction condition of pond sediment (Wilding, ). The redox potential of lower than −206 mV significantly reduces the DO concentration in the SWI and increases the H 2 S in the water column (Wiyoto, Sukenda, Harris, Nirmala, & Djokosetiyanto, ), which affects the total concentration of some major elements.…”
Section: Introductionmentioning
confidence: 99%
“…The pH value change in the water can be caused by the sediment condition (Saraswathy et al, 2019). Several sediment quality parameters that influences the water pH value is sediment redox potential (Wiyoto et al, 2016), sediment pH value, and organic matter contents. A higher soil pH value in the pond soil and dry soil combination was thought due to reactions between two soil types that affected the water pH value.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring is important as a successful key in shrimp culture activities (Xiao et al, 2017;Mohanty et al, 2018;Zainuddin et al, 2019;Rozario & Devarajan, 2021). Monitoring contains shrimp growth, shrimp health, water quality (Encinas et al, 2017;Zainuddin et al, 2019), and pond sediments based on the redox potential, total P, total S, total Mn, and other mineral contents (Wiyoto et al, 2016;Widigdo et al, 2018). In addition to water quality parameters, the sediment conditions are important parameters to observe (Hidayati et al, 2021;Saraswathy et al, 2019;Zeng et al, 2021), as shrimps are benthic organisms (Zhang et al, 2019) that are abundant on the pond base.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident by the increase in organic carbon content in pond soil from 0.2% at DOC 22 to 0.41 % at harvest time. Wiyito et al [4] studied the effect of redox potential in which it was found that negative redox potential generates reduced compounds specifically when the redox value is above -200 mV. It reduces the dissolved oxygen concentration in SWI and increases the sulfide concentration in water column.…”
Section: Changes In Physico-chemical Parameters Of Water and Soilmentioning
confidence: 99%
“…Walker and Winton, [3] explained that poor soil and water quality along with bacterial and viral pathogens are the main cause for mortalities in shrimp industry. High nutrients load derived from left over feed and fecal materials that accumulate on pond bottom are a major concern, which leads to the formation of toxic compounds like NH 3 , NO 2 and H 2 S. These toxic compounds deteriorate the water and soil quality, causing physiological stress thereby reducing the immunity of cultured animal [4].…”
Section: Introductionmentioning
confidence: 99%